Analysis of Consumer Awareness on Twitter Communication and Brand Equity of Bear Brand Milk - Handayanto, A J (Journal of Research in Marketing (ISSN: 2292-9355), 2016)
Social media has become a favourite non-conventional marketing media. Important aspects in social media are word of mouth (WOM) and the number of communication form and conversation between different parties. Bear Brand milk is a product built by its consumer through WOM. The objectives of this study were to analyze consumer awareness on Bear Brand milk communication program in twitter, and to analyze the relation between twitter communication and brand equity from Bear Brand milk. The method used in this study was a descriptive method to answer questions in problem statement which was a non-hypothesis testing. The data collection process was a questionnaire spreading through email toward consumer that used social media and consume Bear Brand milk. The sample collection technique was a non-probability sampling method through convenience sampling. The results showed that from 125 respondents, 88 respondents (70,4%) were aware of the communication conducted by Bear Brand milk and then from that 88 respondents, 58 respondents (65.9%) continued with a reaction towards its communication. The respondents reaction toward Bear Brand milk communication was consider as the spread from word of mouth. The overall results of this study showed that there was a relationship between communication through twitter social media with brand equity which consisted of brand awareness, brand association, quality preception and brand loyalty.